Importance of atomic physics in verification of experimental results and diagnostics of solar and astrophysical observations - Anand K Bhatia (Annals of Mathematics and Physics - Peertechz Publications, 2022)
Accurate results are needed to confirm the experimental results of various atomic processes and analyze the solar and astrophysical observations of intensities of emission lines to infer plasma parameters like electron density, electron temperature and element abundance. A number of theories have been developed over the years to calculate phase shifts when electrons and positrons are scattered from targets. We discuss in this article the recent hybrid theory which has been applied to scattering processes, resonances and photoabsorption process, which is a bound-free transition.